Process of change in organisations through eHealth: 2nd International eHealth Symposium 2010, Stuttgart, Germany, June 7 - 8, 2010 ; Proceedings edited by Stefan Kirn - Stefan Kirn (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2010)
Foreword: On behalf of the Organizing Committee, it is my pleasure to welcome you to Hohenheim, Stuttgart for the 2nd International eHealth Symposium which is themed 'Process of change in organisations through eHealth'. Starting with the inaugural event in 2009, which took place in Turku, Finland, we want to implement a tradition of international eHealth symposia. The presentations and associated papers in this proceedings give a current and representative outline of technical options, application potentials, usability, acceptance and potential for optimization in health care by ICT. We are pleased to present a high-quality program. This year we convey a unique opportunity for academic researchers and industry practitioners to report their state-of-the-art research findings in the domain of eHealth. The symposium aims to foster the international community by gathering experts from various countries such as Australia, Great Britain, Finland and Germany. A first step is done by this symposium which considers this interaction and delivers an insight into current advances made and open research questions. The organizers would like to take the opportunity to thank all the people which made the Symposium possible. We are pleased if both attendance to the 2nd International eHealth Symposium 2010 and reading of this proceedings give you answers to urging questions, a basis for critical discussions, references on interesting tasks and stimulations for new approaches. Table of Contents: Martin Sedlmayr, Andreas Becker, Hans-Ulrich Prokosch, Christian Flügel, Fritz Meier: OPAL Health - A Smart Object Network for Hospital Logistics // Rajeev K. Bali, M. Chris Gribbons, Vikraman Baskaran, Raouf NG Naguib: Perspectives on E-Health: the human touch // Falk Zwicker, Torsten Eymann: Why RFID projects in hospitals (necessarily) fail. Lesson from comparative studies // Nilmin Wickramasinghe, F. Moghimi, J. Schaffer: Designing an intelligent risk detection framework using knowledge discovery techniques to improve efficiency and accuracy of healthcare care decision making // Volker Viktor, Heiko Schellhorn: In search of an appropriate service model for telehealth in Germany // Simone Schillings, Julia Fernandes: Towards a reference model for telemedicine // Reima Suomi: Towards rewards awareness in health care information systems // Manuel Zwicker, Jürgen Seitz, Nilmini Wickramasingh: Adaptions for e-kiosk systems to develop barrier-free terminals for handicapped persons
urn:nbn:de:bsz:100-opus-4797
Keywords: 330; E-Health; Organisation; Deutschland